Landschaft und Wirtschaft in Louisiana unter französischer Kolonialverwaltung - Blume, Helmut (ERDKUNDE, 1956)
During the time of the French administration, economic development advanced slowly in Louisiana. This can be explained by the fact that the natural endowments of the country, especially the alternation between hot and humid summers and at times very cold winters, had made it impossible to find mitable plantation crops within a short time. Furthermore the inconsistency in the methods of the Compagnie des Indes and later of the French crown was a considerable handicap to the economic development. After it was found that no vast financial gains could be achieved in Louisiana, according to the French mercantilistic economic policy, no particular interest was taken in promoting the development of the colony. During this period two types of agricultural enterprises developed in Louisiana, on the one hand fairly arge plantations using slave labour and producing indigo for export, on the other hand peasant holdings growing mainly rice and maize and thus contributing to the supplies of the city of New Orleans and the military forces. Today the most pronounced features of the rural scene which date from the colonial period are firstly the restriction of the cultivated land to one strip, protected by levees, which runs along either bank of the river and its respective tributaries, secondly the division of this land into long lots running perpendicular to the river, and thirdly the juxtaposition of large estates and small-holdings.